Aquinas on Transubstantiation : The Real Presence of Christ in the Eucharist - Hütter, Reinhard, 1958- (Book collections on Project MUSE., 2019)
"This book reexamines Thomas Aquinas's teaching on Eucharistic transubstantiation, arguing that it is an exercise of sacra doctrina (holy teaching) that intends to demonstrate in theology and support with philosophy the simple idea that "transubstantiation" affirms the truth of Christ's words at the Last Supper. As well as delving into Aquinas's own writings, the author incorporates insights of modern theologians and the recent teachings of the Catholic Church"--